EFEKTIVITAS TRANSFORMASI BIROKRASI ERA DIGITAL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAKASSAR - Indah Sabri, Alifyah Nur; Setiawati, Budi; Taufik, Ahmad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of the research is to determine the effectiveness of digital era bureaucratic transformation in public services at the Makassar City Population and Civil Registration Service. This type of research uses qualitative methods with descriptive research type, data collection techniques through observation, interviews and documentation. The results of the research show the transformation of digital era bureaucracy in public services at the Makassar City Population and Civil Registration Service. Achievement of goals has been very effective and has international standards which makes public services easier for the community. Digital-based services will of course provide more significant service improvements. Integration into application-based service programs can be said to be effective because it is cost-effective, time-saving and energy-saving. Adaptation to the online application service program is flexible because people can easily get services and access them